2005
DOI: 10.1104/pp.105.070128
|View full text |Cite
|
Sign up to set email alerts
|

ABA-Hypersensitive Germination3Encodes a Protein Phosphatase 2C (AtPP2CA) That Strongly Regulates Abscisic Acid Signaling during Germination among Arabidopsis Protein Phosphatase 2Cs

Abstract: The phytohormone abscisic acid (ABA) regulates physiologically important developmental processes and stress responses. Previously, we reported on Arabidopsis (Arabidopsis thaliana) L. Heynh. ahg mutants, which are hypersensitive to ABA during germination and early growth. Among them, ABA-hypersensitive germination3 (ahg3) showed the strongest ABA hypersensitivity. In this study, we found that the AHG3 gene is identical to AtPP2CA, which encodes a protein phosphatase 2C (PP2C). Although AtPP2CA has been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
294
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(315 citation statements)
references
References 63 publications
11
294
0
8
Order By: Relevance
“…The results further suggest that PLDa1 is not needed for ABA-induced stomatal closing when ABI1 is deleted. These findings are interesting in light of these and other recent findings that several PP2Cs function as negative regulators of ABA signaling (Leonhardt et al, 2004;Saez et al, 2004;Kuhn et al, 2006;Yoshida et al, 2006), but deletion of the ABI1 PP2C is sufficient to restore PLDa1-independent ABAinduced stomatal closing in plda1 (Mishra et al, 2006). Finally, we show here that the abi1-2 and abi1-3 knockout lines show enhanced ABA-induced stomatal closing.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The results further suggest that PLDa1 is not needed for ABA-induced stomatal closing when ABI1 is deleted. These findings are interesting in light of these and other recent findings that several PP2Cs function as negative regulators of ABA signaling (Leonhardt et al, 2004;Saez et al, 2004;Kuhn et al, 2006;Yoshida et al, 2006), but deletion of the ABI1 PP2C is sufficient to restore PLDa1-independent ABAinduced stomatal closing in plda1 (Mishra et al, 2006). Finally, we show here that the abi1-2 and abi1-3 knockout lines show enhanced ABA-induced stomatal closing.…”
Section: Discussionsupporting
confidence: 54%
“…According to the dramatic effect of the combined loss-of-function phenotype, ABI1 and HAB1 must cooperate to negatively regulate ABA signaling at the seed and seedling stage. Another PP2C, PP2CA, was recently shown to strongly and negatively regulate ABA signaling during germination (Kuhn, et al, 2006;Yoshida et al, 2006). The ABA-mediated seed germination phenotype of pp2ca or hab1-1 abi1-2/hab1-1 abi1-3 mutants was apparent even though HAB1 and ABI1, or PP2CA, respectively, were functional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, expression of genes that encode a group of Ser/Thr PP2Cs, such as ABI1, ABI2, AtPP2CA, HAB1, and HAB2, was suppressed in 35S:AtMYB44 plants and enhanced in atmyb44 knockout plants. These proteins belong to group A PP2Cs (Schweighofer et al, 2004) and have been described as negative regulators of the ABA signal transduction cascade (Gosti et al, 1999;Merlot et al, 2001;Tahtiharju and Palva, 2001;Sáez et al, 2004;Kuhn et al, 2006;Yoshida et al, 2006). The abi1 and abi2 mutations lead to phenotypic alterations in ABA-resistant seed germination and seedling growth, reduced seed dormancy, abnormal stomatal regulation, and defects in various responses to drought stress (Leung et al, 1997;Merlot et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Among seventy-six PP2Cs encoded in the Arabidopsis genome, ABI1, ABI2, HAB1, HAB2, and AtPP2CA are members of group A PP2C, which possibly functions in the regulation of ABA signaling (Schweighofer et al, 2004). Transgenic plants overexpressing these PP2Cs typically show ABA-insensitive phenotypes such as slow stomata closure and enhanced seed germination by exogenously applied ABA, while the knockout lines of these genes exhibit ABA-hypersensitive phenotypes (Yoshida et al, 2006b). Recent studies indicated that negative regulation by the ABI1-related PP2Cs plays a central role in ABA signaling through signal perception and transduction mediated by ABA receptors (Ma et al, 2009;Park et al, 2009).…”
mentioning
confidence: 99%